Effect of Ordo in Assessment of Financial and Non-Financial Information - Helmina, Monica Rahardian Ary; Ghozali, Imam; Isgiyarta, Jaka; Sutomo, Ibnu (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This research focuses on investor decision making on information provided by the company. Belief-adjustment models emphasize the order of presentation of information. Order effects occur when decisions made by individuals differ after receiving evidence in a different order. In order of evidence, the characteristics of the evidence are mixed between confirmative (positive) information and unconfirmed (negative) information.The participants of this study are investors who have investment accounts. The design of the 2x4 experimental method is divided into analysis of factor 2 (presentation pattern) x 4 (information value), which aims to test that the presentation of information in step by step (SBS) will have a better impact than end of sequence (EOS). There are 8 combinations of instruments contain patterns and information values that are used as a source of stock valuation. ANOVA analysis is used for this study. The results showed that there was an effect of the pattern of information delivery in investment decision making when the SBS and EOS disclosure patterns in hypothesis 1 and hypothesis 2. The results of hypothesis 3 did not support the belief adjustment model theory.